Tratamiento de la parálisis general progresiva por el método de Wagner Von Jauregg (conclusión) - Pardo Figueroa, Pedro (1926)
We have insisted enough on very questionable concerning dangers and contraindications pyrotherapy, so not particularly insist on this. It is well known that well-compensated cardiac lesions resistant malarial treatment, provided they are well clarified the degree of severity of aortitis so prevalent in the general paralytics.